Kepentingan Diri dan Martabat Manusia - Pranowo, Yogie (Parahyangan Catholic University, 2023)
This research aims to thoroughly examine the concept of self-interest, human dignity, and the views of the Catholic Church in Indonesia. In the current era of disruption, individuals often pursue the maximization of their self-interests by any means necessary. This condition tends to lead individuals to look down upon others. The research adopts a qualitative methodology based on a literature review. The metadata for this study is sourced from books, online journals, and other secondary sources. The results indicate that by contemplating the meaning of self-interest and human dignity in accordance with Catholic Social Teaching, individuals can reconcile their desires for worldly domination. Thus, this research can contribute to the development of human quality of life in alignment with the teachings of the Church